A dissipated energy model of shock evolution in the simulation of the dynamics of DGM's of railway compositions. (April 2019) - Eckert, Jony Javorski; Ramos, Paola Gonzalez; Oliveira Junior, Alberto Jorge Sales de; Martins, Thiago da Silva; Kurka, Paulo Roberto Gardel
Highlights: A new approach to represent in train draft gear transition forces. Fast and stable numerical solution for longitudinal dynamics simulation. Force transition is represented by the actual physical dissipated energy. Abstract: One of the major challenges for the simulation of the longitudinal dynamics of heavy-haul trains is modeling the in-train forces. The freight cars draft gear mechanisms (DGM) are known for its highly non-linear behavior, with fast force transitions between the loaded and unloaded operational stages. Accurate models that represent the constructive characteristics of DGMs, including friction simulation, demand high computational power and are not viable for the simulation of long trains with several freight cars. To overcome such an issue, simplified models were developed to estimate in-train forces based on intermediate stiffness and/or smoothing techniques that ensure numerical stability and low computational cost for the model. In this paper, a new technique to calculate the DGM intermediate transition forces, based on the dissipated energy approach is developed. The proposed methodology is compared to two well-known techniques presented in the literature and the results show expressive improvement in computational cost and numerical stability of in-train forces estimation.